Exploring the relationship between mediterranean diet adherence and subjective well-being among Greek and Cypriot adults - Deligiannidou, G.E. (2024)
Associations between subjective well-being (SWB) and dietary habits, employment status, and habitual activities are increasingly capturing the focus of researchers as well as policymakers worldwide. This study aimed to explore these associations in a sample of the population in Greece and Cyprus via an online survey. In total, 936 questionnaires (470: Cyprus, 466: Greece) were analyzed to study the associations between the Mediterranean Diet (MD) (using the 14-item MEDAS score, (14-MEDAS)), subjective well-being (SWB), and several socioeconomic factors. Key remarks of this survey highlight the positive impact of MD adherence on some well-being items. Namely, statistically significant differences were found on the following items: Satisfied with life (p < 0.001), Life worthwhile (p < 0.001), Feeling happy (p < 0.001), worried (p = 0.005), and depressed (p = 0.001), when comparing Low MD adherence (14-MEDAS < 5) to High MD adherence (14-MEDAS > 10). Other lifestyle habits such as spending time with friends and family, spending time in nature, and habitual physical activity were associated with aspects of SWB such as Life satisfaction, Life worthwhile, Feeling happy, and energetic. The findings support adherence to the MD, since it is associated with higher life satisfaction and self-reported happiness in this sample and should be considered when developing health policies on well-being.